Perception of Pictographic Alternative Communication Systems in Disorders of Intellectual Development - P.A. Belimova; O.V. Zashchirinskaia (Клиническая и специальная психология)
Alternative communication is an assistive communication tool for people with communication disorders. Because of the variety of alternative communication symbols' graphic representation, it is important to evaluate both classical and unstudied symbolic systems from the perspective of their effectiveness in compensating communication difficulties for persons with disorder of intellectual development. This article deals with the specifics of visual perception and interpretation of concept-nouns and concept-verbs as elements of pictographic alternative communication. The sample of the study (N=92) consists of high school students at special education schools aged 13 to 19 years (M=15.5; SD=1.18), 72% are male. The study's stimulus material was composed of pictogram interpretation tasks in a verbal context and included symbols from three alternative communication languages: Blissymbolics, LoCoS ©, and Pictogram. The analysis of associative interpretations has shown that the factor of pictogram belonging to the particular system affects the correct interpretations of students with mild disorder of intellectual development (p=0.008), as well as the parameters of eye-movement activity: the number of gazes returns to pictograms (p=0.007), number of fixations (p=0.018) and viewing time (p=0.037). We conclude that, considering the cognitive characteristics of students with mild disorder of intellectual development, simpler graphic forms have the greatest efficiency in conveying information, regardless of the part of speech or level of schematism.